2023
DOI: 10.3390/min13091163
|View full text |Cite
|
Sign up to set email alerts
|

Metallogenic Model and Prospecting Progress of the Qiandongshan–Dongtangzi Large Pb-Zn Deposit, Fengtai Orefield, West Qinling Orogeny

Ruiting Wang,
Zhenjia Pang,
Qingfeng Li
et al.

Abstract: The Qiandongshan–Dongtangzi large Pb-Zn deposit is located in the Fengxian–Taibai (abbr. Fengtai) polymetallic orefield. The ore bodies primarily occur within and around the contact surface between the limestone of the Gudaoling Formation and the phyllite of the Xinghongpu Formation, which are clearly controlled by anticline and specific lithohorizon. Magmatic rocks are well developed in the mining area, consisting mainly of granitoid plutons and mafic–felsic dikes. Previous metallogenic geochronology studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Most previous studies suggested that the Pb-Zn mineralization resulted from Devonian sedimentary-exhalative processes. New geochronologic, stable and radiogenic isotopic, and trace element data indicate that the representative Qiandongshan-Dongtangzi Pb-Zn deposit is not the product of sedimentary-exhalative processes, but is rather the product of epigenetic magmatic hydrothermal fluid processes, driven by regional tectono-magmatic activities in the Late Triassic Epoch [4,5].…”
mentioning
confidence: 99%
“…Most previous studies suggested that the Pb-Zn mineralization resulted from Devonian sedimentary-exhalative processes. New geochronologic, stable and radiogenic isotopic, and trace element data indicate that the representative Qiandongshan-Dongtangzi Pb-Zn deposit is not the product of sedimentary-exhalative processes, but is rather the product of epigenetic magmatic hydrothermal fluid processes, driven by regional tectono-magmatic activities in the Late Triassic Epoch [4,5].…”
mentioning
confidence: 99%